2016
DOI: 10.3390/molecules21050632
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of the Mannich Base(1,3-bis-((3-Hydroxynaphthalen-2-yl)phenylmethyl)urea) on Hepatocellular Carcinoma

Abstract: Abstract:The present study was designed to evaluate the antitumor effects of the synthetic Mannich base 1,3-bis-((3-hydroxynaphthalen-2-yl)phenylmethyl)urea (1,3-BPMU) against HEP-G2 hepatoma cells and diethylnitrosamine (DEN)-induced hepatocarcinoma (HCC) in albino rats. In vitro analysis results revealed that 1,3-BPMU showed significant cytotoxicity and cell growth inhibition in HEP-G2 hepatoma cells in a concentration-dependent manner. Furthermore, flow cytometry results indicated that 1,3-BPMU enhanced ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…This deterioration may account for the excessive free radicals because of DEN metabolism that caused HCC. In a good agreement with the present findings, Hussain et al [75] ; Zhao et al [120]; Kadasa et al [60]; Chidamabaram et al [121]; Vedarethinam et al [122], investigated that DEN-treated rats showed an unformatted architecture, the presence of inflammatory cells along the central vein and enlarged nuclear size in the liver cells.…”
Section: Discussionsupporting
confidence: 91%
“…This deterioration may account for the excessive free radicals because of DEN metabolism that caused HCC. In a good agreement with the present findings, Hussain et al [75] ; Zhao et al [120]; Kadasa et al [60]; Chidamabaram et al [121]; Vedarethinam et al [122], investigated that DEN-treated rats showed an unformatted architecture, the presence of inflammatory cells along the central vein and enlarged nuclear size in the liver cells.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed significant decrease in Casp-3 level in DEN group compared to normal animals as reported before. 39 Treatment with cis -platin and Pt NPs resulted in increase in Casp-3 level compared to DEN rats. These results are in consonance with previous studies, which indicates that both treatments induced apoptosis as reflected by increase in Casp-3 level.…”
Section: Discussionmentioning
confidence: 94%
“…Herein, the high activity of 5 -NT in the DENA-CCl4 intoxicated rats are revealing of intrahepatic obstruction of bile canaliculi as a result of liver cell injury and due to increase in the fluidity of the cell membrane as confirmed by Ghaffar [50]. Moreover, Vedarethinam et al [51] reported that the elevated levels of the 5 -NT marker enzyme in rats injected by DENA are correlated with the malignancy development of DENA action.…”
Section: Discussionmentioning
confidence: 78%
“…The present results were in the same line of Tawfek et al [58] who stated that induction of DENA-CCl4 caused an elevation in the AFP level, suggesting the occurrence of premalignant liver changes. Similarly, Vedarethinam et al [51] stated that induction of DENA induced liver damage as documented by an increase in AFP.…”
Section: Discussionmentioning
confidence: 95%